Importance of Financial literacy For Sustainable Future Environment: A Research Among People In Rural Areas With Special Reference To Mandi District,Himachal Pradesh - Kumari, Sunita; Harikrishnan, Ampu (International Journal of Engineering, Science and Information Technology, 2021)
Education and Role of technology is a right combination that allows the people to make the right decision for sustainable development. It has been observed that financial education is a challenge globally. Financial education plays fundamental role for better understanding the needs of combat climate change. Education and Environmental awareness are important to create global networks among the different corporation that include public and private sectors. Financial literacy is closely connected with sustainable growth of economy. Sustainable behaviors of individuals are required for ensuring the sustainable development in the society. This paper is to discuss the importance of financial literacy for sustainable future Environment. It deals with the concept of financial literacy, sustainable development and to study the respondent demographic profile as well as the knowledge about financial literacy for sustainable future environment. The paper is designed is on Primary data and secondary data. Primary data is collected through survey. A questionnaire is used which is most common tool for collection of data. Secondary data is gathered through various reports, Articles, journals or through literature review focus on financial literacy for sustainability.This paper analysis important of financial literacy for sustainable future environment with special reference to Rural people of particular District of Himachal Pradesh. This study has covered only one district of Himachal Pradesh.